Dark Reflections: Jacques Lacan and the doppelgänger of American identity - Hodgdon, Emma Y. (Tufts Archival Research Center, 2019)
An analysis of the doppelgänger tradition as inflected within literature from the American Renaissance period. Using Jacques Lacan's mirror stage theory as context, I analyze how the doppelgänger explores the fracturing of American identity along political, racial, and idealistic lines through three main texts (Edgar Allan Poe's short story, "William Wilson," John Neal's novel, "Logan," and Nathaniel Hawthorne's short story, "Alice Doane's Appeal"), and how such revelatory dissolution of constitutional ideals is not the end of identity, but its engine.